2014
DOI: 10.1038/bmt.2014.106
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal photopheresis for treatment of adults and children with acute GVHD: UK consensus statement and review of published literature

Abstract: Extracorporeal photopheresis (ECP) has been used for over 20 years to treat acute GVHD (aGVHD) and chronic GVHD. Evidence on the efficacy of response in aGVHD has continued to accrue and data suggest that there is a good response and prolonged survival in both children and adults with grade II-IV aGVHD. Unlike chronic GVHD where treatment schedules are typically one or two times monthly for 12-18 months, patients with aGVHD respond rapidly to an intense weekly treatment schedule for 8 weeks, typically allowing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…The incidence of grade II–IV aGvHD in children ranges from 28 to 56% (49), depending on the degree of histocompatibility, recipient age, underlying condition, and conditioning regimen used (50). Higher aGvHD grades have consistently been associated with worse transplant-related mortality (TRM) and lower overall survival rates (51). …”
Section: Graft-versus-host Diseasementioning
confidence: 99%
“…The incidence of grade II–IV aGvHD in children ranges from 28 to 56% (49), depending on the degree of histocompatibility, recipient age, underlying condition, and conditioning regimen used (50). Higher aGvHD grades have consistently been associated with worse transplant-related mortality (TRM) and lower overall survival rates (51). …”
Section: Graft-versus-host Diseasementioning
confidence: 99%
“…Extracorporeal photopheresis is by UK and Italian scientific/clinical consensus groups recommended as 2 nd -line treatment for graft-versus-host disease (GvHD) after allogeneic stem cell transplantation and for scleroderma and other autoimmune diseases. 300 Because of the high costs, however, many patients cannot be treated with extracorporeal photopheresis.…”
Section: European Research Contributionsmentioning
confidence: 99%
“…A meta-analysis based on nine relevant prospective studies showed a pooled overall response rate of 0.69 (skin 0.84, gut 0.65, liver 0.65) [37]. A Recent review reports similar results in response with an impact of ECP response on overall survival in multivariate analysis that is much more meaningful for clinical practice [39]. We also have to consider that the complexity of using and evaluating ECP in aGVHD is related to the delayed onset of ECP, delayed action and the necessity of combined immunosuppression.…”
Section: Graft Versus Host Disease: More In Chronic Than In Acute Gvhd?mentioning
confidence: 53%